The Heterogeneous Flexible Periodic Vehicle Routing Problem: Mathematical formulations and solution algorithms - Huerta-Muñoz, Diana L.; Archetti, Claudia; Fernández, Elena; Perea, Federico (Computers & operations research, 2022)
The aim of this paper is to introduce the Flexible Periodic Vehicle Routing Problem with Heterogeneous Fleet, a variant of the Periodic Vehicle Routing Problem. Flexibility is introduced in service schedules and delivered quantities, heterogeneity comes from different vehicles capacities and speeds. Three Mixed-Integer Linear Programming formulations and a matheuristic, based on Kernel Search, are proposed. Computational tests are made to evaluate the performance of the three formulations and to assess the quality of the solutions provided by the matheuristic. •The Heterogeneous Flexible Periodic Vehicle Routing Problem (HFPVRP) is introduced.•In the HFPVRP, speeds and capacities of vehicles may differ.•Three different mathematical formulations are proposed to represent the HFPVRP.•A Kernel Search matheuristic, denoted as KSHFP, is developed to solve the HFPVRP.•Computational experiments were carried out to evaluate its performance.•Computational results show the quality of solutions found by the KSHFP.